Comparative Study of the CSR Initiatives of Microsoft, IBM, Google, Sun Microsystems and Cisco Systems in the Gulf Region - Sikander, Huzaifa (2008)
An integral part of the MBA degree at University of Nottingham is the management project worth 60 credits which marks the completion of the degree. I got a chance to do my management project with Microsoft Corporation Gulf and was working with three other friends of mine. The project was a comparative study of the Corporate Social Responsibility (CSR) initiatives of Microsoft with IBM, Google, Sun Microsystems and Cisco Systems. I was working in the project with three other friends of mine and it has been a very enriching experience for all of us. This report is a part of the group project in which we had to outline all what happened in the duration of the project from our individual perspective. I have divided the report into four sections. The first section describes how we got the project and how team member were chosen. The second section describes all the research, readings and preparations that we made before going to Dubai and gives a full detailed account of what we did in Dubai. The third part of the report explains about how we compiled all our research into the final group report. Throughout the report there is also a discussion of the obstacles we faced on the way and how we over came them together. In the conclusion I have discussed how everyone contributed towards the project and the fact that the report would not have been the same if we were all not working together on it. It ends with a brief account of my personal experience of this whole management project.